THE EFFECT OF ENVIRONMENTAL SOCIAL GOVERNANCE ON FINANCIAL PERFORMANCE WITH THE COST OF CAPITAL AS AN INTERVENING VARIABLE - Widyo Nugroho, Bernadus Erwin Bagastian; Mulyasari, Windu (Management Science Research Journal, 2025)
This study aims to determine the effect of ESG on financial performance with the cost of capital as an intervening variable. The intervening variable in this study is the cost of capital as measured by the weighted average cost of capital (WACC) based on the company’s annual report. The independent variable in this study is Environmental Social Government (ESG) as measured using Thomson Reuters Eikon. The dependent variable in this study is financial performance as measured by Return Of Asset (ROA). The population of this study in manufacturing and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the2019-2022 period. The sampling technique used in this method is purposive sampling with a total sample of 156 data. The data analysis method in this study uses multiple regression analysis with STATA 17 and path analysis with the help of an online sobel calculator. The results of this study indicate that ESG disclosure has a positive effect on financial performance, environmental disclosure has no significant positive effect on financial performance, social disclosure has no significant positive effect on financial performance, andgovernance disclosure has no significant positive effect on financial performance.In addition, the cost of capital is unable to act as a mediator in the effect of ESG on financial performance.